Effect of abiotic factors on the respiration intensity of fruit vegetables during storage - Priss, Olesia; Yevlash, Viktoria; Zhukova, Valentina; Kiurchev, Sergey; Verkholantseva, Valentуna; Kalugina, Iryna; Kolesnichenko, Svetlana; Salavelis, Alla; Zolovska, Olena; Bandurenko, Halyna (Eastern-European Journal of Enterprise Technologies, 2017)
The influence of abiotic factors on the respiration intensity of vegetables during storage is investigated. Considerable variability of respiratory metabolism was established over the years of research for cucumbers (27.51 %), zucchini (36.40 %) and pepper (exceeding 37 %); it is the lowest for tomato (up to 13.29 %). For all vegetables, regardless of the varietal specificity, we found a positive correlation between the intensity of respiration and the total of active temperatures during fruit formation period. The inverse correlation was established between respiratory activity and the amount of precipitation during vegetation season. A two-factor variation analysis revealed that the influence of abiotic factors on the level of respiration is essential, varying from 24.29 to 90.68 %. We analyzed the degree of influence of varietal and species specificity on the intensity of respiration. It was found that this indicator plays a key role in respiratory activity. Vegetables that are treated thermally with antioxidants are characterized by the deeper delay in respiratory activity. For tomatoes, thermal treatment can reduce the level of climactericx by 9 % compared to control. The duration of storage of the treated vegetables is extended by 1.3–1.7 times